Early healing pattern of autogenous bone grafts with and without e-PTFE membranes: A histomorphometric study in rats - Jardini, Maria Aparecida Neves [UNESP]; Marco, Andrea Carvalho de; Lima, Luiz Antonio (My University, 2005)
Objective. The aim of this study was to perform quantitative and qualitative analyses of the initial repair pattern of an autogenous bone block graft when covered or not with e-PTFE membranes. Study design. Sixty male Wistar rats received a bone graft plus an e-PTFE membrane (MB) or just the graft (B). A block graft was harvested from the animal's calvarium and was laid and stabilized on the external cortical area near the angle of the mandible. Descriptive histology and histomorphometric analyses were carried out and the data were analyzed statistically by ANOVA and the Tukey test, with the level of significance set at 5%. Results. The results for group B showed that there was bone loss during the healing period (B0 = 1.38, B45 = 1.05, F = 7.91 > F C = 3.02), that is, the initial volume of the graft decreased in time. Bone tissue loss was about 24%. In contrast, the MB group showed bone tissue gain along the observation period (MB0 = 1.54, MB45 = 2.40, F = 7.91 > FC = 3.02), meaning that the total volume of newly formed bone was greater than the original graft area. Bone tissue gain was approximately 55%. MB showed significantly greater bone gain when compared to B (B45 = 1.05, MB45 = 2.40, F = 39.86 > FC = 1.90). These significant differences between B and MB could already be observed after 21 days. Conclusions. The bone block graft underwent resorption at an early healing stage, while additional new bone formation was observed when the bone graft was covered with an e-PTFE membrane. © 2005 Mosby, Inc. All rights reserved.
Keywords: politef; analysis of variance; animal; artificial membrane; bone regeneration; bone transplantation; comparative study; male; mandible; methodology; nonparametric test; oral surgery; osteolysis; periodontics; randomization; rat; Wistar rat; Analysis of Variance; Animals; Bone Regeneration; Bone Resorption; Bone Transplantation; Guided Tissue Regeneration, Periodontal; Male; Mandible; Membranes, Artificial; Oral Surgical Procedures; Polytetrafluoroethylene; Random Allocation; Rats; Rats, Wistar; Statistics, Nonparametric